If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2v + 5)(2v + -5) = 0 Reorder the terms: (5 + 2v)(2v + -5) = 0 Reorder the terms: (5 + 2v)(-5 + 2v) = 0 Multiply (5 + 2v) * (-5 + 2v) (5(-5 + 2v) + 2v * (-5 + 2v)) = 0 ((-5 * 5 + 2v * 5) + 2v * (-5 + 2v)) = 0 ((-25 + 10v) + 2v * (-5 + 2v)) = 0 (-25 + 10v + (-5 * 2v + 2v * 2v)) = 0 (-25 + 10v + (-10v + 4v2)) = 0 Combine like terms: 10v + -10v = 0 (-25 + 0 + 4v2) = 0 (-25 + 4v2) = 0 Solving -25 + 4v2 = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 4v2 = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 4v2 = 0 + 25 4v2 = 0 + 25 Combine like terms: 0 + 25 = 25 4v2 = 25 Divide each side by '4'. v2 = 6.25 Simplifying v2 = 6.25 Take the square root of each side: v = {-2.5, 2.5}
| 2(-2)-3(4)-4(-1)= | | X^2(8-X^2)=0 | | 2d-31=-9d+24 | | x+.6x=5 | | 176-4x=32x+20 | | (x)(x+2)=68 | | 13p^2=24 | | x+14=114 | | 13p^2=0 | | 5(x+3)=70 | | 5g-3=7 | | 0=150-5x-x^2+117 | | -4.1-5x-1.4-x=-5x-1.2 | | (x-4)8=16 | | 3f+5=17 | | x=22-3.5x | | 5x-5=8-7x | | 9x-(2x+7)=3x-43 | | 0=250-9x-x^2+112 | | 2tanx=0 | | x+7x-44=0 | | 23/4+6= | | (15-0.5p)(p-2)=10 | | .5(x+2)-.2(x-8)=0 | | x^2+x+5=x+10 | | 3.5+.75= | | 5x-3x=-1-4 | | (x)+(x+1)=19 | | 31/2+3/4= | | 2(3y+2)=5(2y-4) | | P=a+b+3c | | 4a+3=9 |